Liver cancer oncogenomics: opportunities and dilemmas for clinical applications - Marquardt, Jens U (Hepat Oncol, 2015)
Primary liver cancers are among the most rapidly evolving malignant tumors worldwide. An underlying chronic inflammatory liver disease, which precedes liver cancer development for several decades and frequently creates a pro-oncogenic microenvironment, impairs progress in therapeutic approaches. Molecular heterogeneity of liver cancer is potentiated by a crosstalk between epithelial tumor and stromal cells that complicate translational efforts to unravel molecular mechanisms of hepatocarcinogenesis with a drugable intend. Next-generation sequencing has greatly advanced our understanding of cancer development. With regards to liver cancer, the unprecedented coverage of next-generation sequencing has created a detailed map of genetic alterations and identified key somatic changes such as CTNNB1 and TP53 as well as several previously unrecognized recurrent disease-causing alterations that could contribute to new therapeutic approaches. Importantly, these investigations indicate that a classical oncogene addiction cannot be assumed for primary liver cancer. Therefore, hepatocarcinogenesis can be considered a paradigm suitable for individualized medicine.